The wife’s right to husband’s property earned upon marriage: A juristic study - Abdelgayed, Ahmed Fathi Ramdan; Soliman, Ragab Abou Melih Mohamed; Salem, Khobaib Ali Saeed; Elbahrawi, Salah Mohamed Moustafa Moustafa (Linguistics and Culture Review, 2021)
There are rising voices at present calling for the wife’s sharing ownership of her husband’s property that is earned during their marital relationship, on the premise that such property is earned due to the mutual effort of both spouses, with the wife carrying out house chores and thus allowing the husband time to work, or with both having jobs and contributing to the welfare of the family and maximizing their property. Some countries legalized such matrimonial property, binding the husband to share with his wife whatever he earns during their marital relationship. In this study, I examined the corroborating proofs of such a stance and concluded that each spouse is independent in terms of ownership, wealth, income, and disposal. I also concluded that financial transactions between the spouses are liable to legal rulings on financial transactions in general and that if the two spouses dispute the ownership of any property, the claimant is bound to prove the validity of such a claim.